HISTORICAL LANDSLIDES IN THE PREFECTURE OF IOANNINA – COLLECTION AND ANALYSIS OF DATA - Kalantzi, F.; Doutsou, I.; Koukouvelas, I. (Bulletin of the Geological Society of Greece, 2010)
The present study assessed landslide events over a time span of fifty years in the prefecture of Ioannina. Historical data analysis commonly provides valuable data for understanding distribution of landslides. The methodology included collection and analysis of articles about landslides events found in the local newspapers between 1960 and 2008, also in the national newspapers (1960-1967) and in the contemporary national newspapers (1995-2008). The time interval selected in this study is representative of the entire time period of systematic newspapers publication. During this time spam, eighty nine historical landslides were identified. Newspaper articles annotate the time and the location of the landslides as well as primarily the role of weather conditions in triggering the landslides. In addition, published articles provide information on the damages caused by the landslides. The study shows that these events occurred due to extremely high precipitation, snowstorms or prolonged rainfall. The monthly distribution of the recorded phenomena shows an increase of landslide events during January-March and November-December, as these are the months with the highest precipitation and snowing in the prefecture. Although time clustering of the landslides within the Ioannina Prefecture in the time interval 1960 to 2006 was found to be repeated every forty years, their spatial clustering appears to change.